2012 11th International Conference on Machine Learning and Applications 2012
DOI: 10.1109/icmla.2012.77
|View full text |Cite
|
Sign up to set email alerts
|

Multi-label Collective Classification Using Adaptive Neighborhoods

Abstract: Abstract-Multi-label learning in graph-based relational data has gained popularity in recent years due to the increasingly complex structures of real world applications. Collective Classification deals with the simultaneous classification of neighboring instances in relational data, until a convergence criterion is reached. The rationale behind collective classification stems from the fact that an entity in a network (or relational data) is most likely influenced by the neighboring entities, and can be classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This process continues until the algorithm converges. Saha et al (2012) have recently described an iterative convergence algorithm to deal with multi-label classification problems. Finally, collective classification has been recently investigated in combination semi-supervised and transductive learning (Shi et al 2011;McDowell and Aha 2012).…”
Section: Collective Inferencementioning
confidence: 99%
“…This process continues until the algorithm converges. Saha et al (2012) have recently described an iterative convergence algorithm to deal with multi-label classification problems. Finally, collective classification has been recently investigated in combination semi-supervised and transductive learning (Shi et al 2011;McDowell and Aha 2012).…”
Section: Collective Inferencementioning
confidence: 99%
“…This process continues until the algorithm converges. Saha et al (2012) have recently described an iterative convergence algorithm to deal with multi-label classification problems. McDowell and Aha (2013) have shown that the accuracy of collective classification performed with both iterative convergence approaches and Gibbs sampling approaches may be increased by including, for each node, the descriptive attributes of the neighboring nodes as relational attributes.…”
Section: Related Workmentioning
confidence: 99%
“…The difference is that it is applied to heterogeneous networks and not to logic clauses. Connections can also be found with the task of multi-label collective classification [23,38], where, however, objects to be classified are of the same type.…”
Section: Introductionmentioning
confidence: 99%